Characterization of a Lab-Scale Process to Produce Whole IgG Antivenom Covering Scorpion Stings by Genus Tityus and Centruroides of Colombia - Sebastian Estrada-Gomez; Vitelbina Núñez; Leidy Johana Vargas-Muñoz; Carlos A. Madrid-Bracamonte; Lina Maria Preciado (MDPI AG, 2022)
Scorpion stings are a public health event in Colombia lacking official epidemiological data, and are considered a medical emergency. Despite the two local producers of antivenoms, neither of them is currently manufacturing scorpion antivenoms. We present the characterization of a lab-scale process to produce the first specific scorpion antivenom for Colombia, formulated to cover scorpion stings produced by Tityus pachyurus, Tityus asthenes, Tityus fuhrmanii, Centruroides spp. To do so, rabbits were immunized by subcutaneous injection with each venom using an immunization program of 3 months. After each rabbit reached the required IgG concentration, rabbits were bled, and plasma was separated by decantation under refrigeration. Immunoglobulins were purified from each hyperimmune plasma using a methodology including precipitation with ammonium sulfate, thermocoagulation, and purification through an ultrafiltration process using a ready-to-use and reusable laboratory crossflow tangential cassette with a polyethersulfone membrane. Each hyperimmune plasma was processed by being separated and freeze-dried at the end of the process. Rabbits were able to produce specific IgG antibodies recognizing the respective immunization venom; even an in vitro interspecies cross-recognition was detected. The separation and purification processes allowed us to obtain IgG products without considerable contaminants (except for albumin). The process was characterized, and critical stages were identified.